KAJIAN PEMGGUNAAN REAKTOR BIOFILTER UNTUK PENGOLAHAN GREYWATER DI KAWASAN PEMUKIMAN ATAS AIR KELURAHAN MARGASARI KOTA BALIKPAPAN MENUJU KONSEP ZERO WASTE - , JEN SUPRIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Settlement on the water Margasari is one type of settlement in the city of Balikpapan as a coastal city. PDAM as the main source of water fulfillment from the city of Balikpapan so required the efficiency of its use . One is by way of Greywater processing in order to be reused for flushing the toilets in order to support the concept of zero waste. The purpose of this study was to obtain data on the composition and potential greywater generated and can be reused by the community, to determine the effectiveness of using a biofilter reactors as an alternative to the greywater treatment unit to the parameters of pH, BOD, COD, TSS, and NH3-N, as well as to identify potential the role of communities in the management of greywater waste leading to the concept of zero waste in the management of domestic wastewater. The results of this study, the potential of greywater which is produced by settlement on water Margasari Balikpapan City, total region water requirement based on PDAM account data is 22.929,29 m3 or based on the water needs of every soul is 785.520 l/day (23.565.600 l/month) total waste is 80% of the total water demand region that is equal to 18.852.480 l/month, and 75% of the total waste will be an greywater that is equal to 14.139.360 l/month. While the need to flush (flushing) toilet 9,489,081.60 l/month so if it can be fully utilized greywater can reduce water consumption by 41.38% of the total water consumption per month. From the results of the research with simple processing biofilter reactors have optimum effectiveness of the parameter BOD decrease is 86.54%, COD is 82.27%, TSS is 84.60%, and NH3-N is 19.99%.